The Urgency of Formalizing Customary Meetings in Kedang Indigenous Communities into Notary Official Deeds - Muhammad Nuha Maulana Pasya; Danang Wahyu Muhammad; Mukti Fajar Nur Dewata (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
This research examines the urgency of recording the results of traditional meetings of the Kedang community in Lembata, East Nusa Tenggara, into notarial deeds to strengthen legal legitimacy and protect the rights of indigenous communities. The method used is qualitative research with a literature review and field observation on implementing customary law and the procedure for making notarial deeds. The research results show that Kedang customary law, rich in tradition and cultural values, is important in regulating social norms and resolving internal conflicts. However, there are significant challenges in integrating customary law with the formal national legal system. The discussion emphasizes the role of Notary officials as mediators who formalize the results of customary meetings, thereby giving them legitimate legal force while respecting customary values. This study recommends the need for regulatory strengthening to accommodate the harmonization of both legal systems to create adequate justice and legal protection for indigenous communities.